Realizing Joint Extreme-Scale Simulations on Multiple Supercomputers-Two Superfacility Case Studies - Pollinger, Theresa; Craen, Alexander Van; Offenhauser, Philipp; Pfluger, Dirk (SC24: International Conference for High Performance Computing, Networking, Storage and Analysis, 2024)
High-dimensional grid-based simulations serve as both a tool and a challenge in researching various domains. The main challenge of these approaches is the well-known curse of dimensionality, amplified by the need for fine resolutions in high-fidelity applications. The combination technique (CT) provides a straightforward way of performing such simulations while alleviating the curse of dimensionality. Recent work demonstrated the potential of the CT to join multiple systems simultaneously to perform a single high-dimensional simulation. This paper shows how to extend this to three or more systems and addresses some remaining challenges: load balancing on heterogeneous hardware; utilizing compression to maximize the communication bandwidth; efficient I/O management through hardware mapping; and improving memory utilization through algorithmic optimizations. Combining these contributions, we demonstrate the feasibility of the CT for extreme-scale Superfacility scenarios of 46 trillion DOF on two systems and 35 trillion DOF on three systems. Scenarios at these resolutions would be intractable with full-grid solvers (\gt1,000 nonillion DOF each).